2022
DOI: 10.1111/ene.15558
|View full text |Cite
|
Sign up to set email alerts
|

How resistant are levodopa‐resistant axial symptoms? Response of freezing, posture, and voice to increasing levodopa intestinal infusion rates in Parkinson disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Five [ 57 59 , 62 , 77 ] of the included studies were interventional studies. The other studies were observational.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five [ 57 59 , 62 , 77 ] of the included studies were interventional studies. The other studies were observational.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies out of 21 investigated solely one subjects' group [ 57 , 59 , 64 , 69 , 70 , 77 ]. Other studies included two [ 58 , 61 , 62 , 66 , 71 , 72 ] or three subjects’ groups [ 60 , 63 , 65 , 67 , 68 , 73 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have analyzed axial symptoms in PD patients with an instrumental approach focusing separately on gait alterations or speech disturbances. However, very few studies have assessed instrumentally the whole spectrum of axial symptoms in PD and suggested the presence of a relationship between spatial-temporal gait and speech parameters [11,12]. Subthalamic nucleus deep brain stimulation (STN-DBS) represents a short-and long-term effective treatment in advanced PD patients.…”
Section: Introductionmentioning
confidence: 99%